2017
DOI: 10.18203/2320-1770.ijrcog20171972
|View full text |Cite
|
Sign up to set email alerts
|

A study of thyroid dysfunction in dysfunctional uterine bleeding

Abstract: Background: The objective of the study was to evaluate the prevalence of thyroid dysfunction in dysfunctional uterine bleeding and to assess the menstrual and endometrial pattern in women with thyroid disorders.Methods: The present study was conducted on 200 patients who presented with dysfunctional uterine bleeding in gynecology OPD.Results: Among the 200 women 39 (19.5%) had hypothyroidism, 2 (1%) had hyperthyroidism and 159 (79.55%) were euthyroid. Menorrhagia was the most common menstrual disorder in hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 8 publications
6
9
1
1
Order By: Relevance
“…Parveen et al also found an incidence of 45% of heavy menstrual bleeding in their study. 25 Women with complaints of shortened cycles were 5% which was similar to in the study by Verma et al and Parveen et al 25,29 Thyroid disorders are common in females with subclinical hypothyroidism as it's the most common type. Menstrual irregularities are seen in both hyperthyroidism as well as hypothyroidism.…”
Section: Discussionsupporting
confidence: 72%
“…Parveen et al also found an incidence of 45% of heavy menstrual bleeding in their study. 25 Women with complaints of shortened cycles were 5% which was similar to in the study by Verma et al and Parveen et al 25,29 Thyroid disorders are common in females with subclinical hypothyroidism as it's the most common type. Menstrual irregularities are seen in both hyperthyroidism as well as hypothyroidism.…”
Section: Discussionsupporting
confidence: 72%
“…The patients with thyroid disorders have comparatively higher mean BMI than the Euthyroid population due to obesity. Menorrhagia as the most common form of AUB pattern in the total population is supported by almost all the studies-Parveen et al (5) Verma et al (6) and Divya et al (7) Both subclinical and overt hypothyroidism associated with Menorrhagia, Acyclical bleeding and Polymenorrhagia as the most common AUB patterns is supported by studies conducted by Bhavani et al (8) and Sanghamitra et al (9) who showed menorrhagia in 73.4% and 62.5% respectively. The cause for Menorrhagia in most of these studies is said to be due multiple factors: Defective or delay in LH response leading to Luteal phase defect and anovulation due to GnRH pulsatile secretion which was due to TRH induced Hyperprolactinemia, Abnormal feedback at pituitary level due to decreased SHBG production thereby leading to altered peripheral metabolism of oestrogens, Altering coagulation factors (decrease in factors VII, VIII, IX, XI) causing Menorrhagia.…”
Section: Discussionmentioning
confidence: 76%
“…Verma et al found that 74.3% of patients with hypothyroidisim had proliferative endometrium. 13 Padmaleela et al found in their study that the common finding in endometrial biopsy both in hypothyroid (60%) and hyperthyroid (57.1%) cases was proliferative endometrium. 14 Cystoglandular hyperplasia was found in 13.3% of hypothyroid patients.…”
Section: Discussionmentioning
confidence: 89%